The Influence of Service Quality on Public Satisfaction and Public Trust: A Study on Jakarta Public Health Services during COVID-19 Pandemic - Citra, Baiq Sany Ayu; Setiono, Bambang; Pangaribuan, Christian Haposan; Ambarwati, Maria Francisca Lies (Journal of Business, Management, and Social Studies, 2021)
Objective – The COVID-19 pandemic has challenged the government because of the uncertainty in public health services’ preparedness to provide patient-centered care that meets public needs. Hence, the necessity to evaluate service quality towards society’s satisfaction and trust during these difficult times. This study examines the influence of service quality towards public satisfaction and public trust on the public health services in Jakarta during the pandemic.Methodology – A quantitative method using regression data analysis with a total sample of 120 respondents.Findings – The result shows that two dimensions of public service quality (empathy and reliability) significantly influenced public satisfaction. However, the other three dimensions of public service quality (tangible, responsiveness, and assurance) did not influence public satisfaction. Only two dimensions of public service quality (reliability and responsiveness) significantly influenced public trust. The result found that public satisfaction positively influenced public trust. The relation was strongest compared to other correlations in the study.Novelty – This study examined public health services by the government of Jakarta during the COVID-19 pandemic.